IMPLEMENTASI LESSON STUDY DALAM UPAYA MENINGKATKAN PROFESIONALISME GURU MATA PELAJARAN IPA SD NEGERI 3 JANGKAR SITUBONDO TAHUN PELAJARAN 2016/2017 - Eko Hadi Purwanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2016)
The teacher is a professional worker, but in reality there are many teachers who do not meet the professional qualifications. Therefore, the professionalism of teachers needs to be improved continuously, with various professional and proportional manners. One of them is implementation of lesson study. This study aimed to provide information and explanation that can be obtained benefits such as: a) improving the professionalism of science teachers through the process of improvement in the ability of the analysis of the problem’s learning; b) promoting creative and innovative teachers in learning process; c) improving quality of learning process that leads to the improvement of the quality of student learning outcomes. This research use descriptive research conducted by three cycles of lesson study in which one cycle consisted of (a) Planning; (b) Action, followed by observation; (b) Reflection; and (d) the next Action Plan. Types of data collected are qualitative data. Process and analysis performed by steps of data reduction, data tabulation, data interpretation and conclusion. From the data process and analysis concluded that the implementation of lesson study on the implementation of effective learning isenhancing the professionalism of teachers. Based on the conclusions of this study can be recommended as one of the solutions the problem of low quality of the learning process conducted by a science teacher at SD Negeri 3 Jangkar